Comparison of the effects of meta-topolin and other cytokinins on chlorophyll and protein contents and peroxidase activity in cucumber cotyledons - Çağ, Serap; ARISAN, ELİF DAMLA (Taylor and Francis Online, 2003)
Cytokinins play an important role in controlling many of the processes that contribute to plant senescence. The aim of this study was to compare the effect of different cytokinins, especially the new aromatic cytokinin meta-topolin (mT), with kinetin (K), benzyladenine (BA), and zeatin (Z) on chlorophyll formation in etiolated cucumber cotyledons. Protein contents and peroxidase activities were also investigated. Exogenous application of cytokinins was effective in stimulating chlorophyll biosynthesis. mT was shown to be the most effective cytokinin in stimulating chlorophyll biosynthesis at low concentrations compared to the other cytokinins. mT treatments at 0.02-0.0002 mg/ml increased the amount of chlorophyll more than threefold compared with control cotyledons. BA stimulated the total chlorophyll content at 0.1-10 mg/ml concentrations, but inhibited at lower (0.01, 0.001 mg/ml) concentrations. K increased the chlorophyll amount at 1 mg/ml concentration to twice that of control cotyledons. Z stimulated the chlorophyll level at almost all the concentrations applied. The effects of the most effective concentrations of cytokinins used in this research on the chlorophyll level and on the protein content were examined. A doubling of protein content in 0.02 mg/ml-mT-treated cotyledons was observed, whereas Z, BA, and K increased the total protein to a lesser extent. BA was shown to have the greatest effect on peroxidase activity.